Exploring charge density analysis in crystals at high pressure: data collection, data analysis and advanced modelling. Issue 4 (1st August 2017) - Casati, Nicola; Genoni, Alessandro; Meyer, Benjamin; Krawczuk, Anna; Macchi, Piero
Abstract : This paper reports on the determination of charge density distributions from crystals compressed at high pressure. Although much less accurate than traditional charge density analysis, these studies provide valuable information because the electronic states of molecules confined in highly condensed space are not easily predictable by theory and therefore experimental validation is a must. Abstract : The possibility to determine electron‐density distribution in crystals has been an enormous breakthrough, stimulated by a favourable combination of equipment for X‐ray and neutron diffraction at low temperature, by the development of simplified, though accurate, electron‐density models refined from the experimental data and by the progress in charge density analysis often in combination with theoretical work. Many years after the first successful charge density determination and analysis, scientists face new challenges, for example: (i) determination of the finer details of the electron‐density distribution in the atomic cores, (ii) simultaneous refinement of electron charge and spin density or (iii) measuring crystals under perturbation. In this context, the possibility of obtaining experimental charge density at high pressure has recently been demonstrated [Casati et al. (2016). Nat. Commun. 7, 10901]. This paper reports on the necessities and pitfalls of this new challenge, focusing on the species syn ‐1, 6:8, 13‐biscarbonyl[14]annulene. The experimental requirements, the expected data quality and data corrections are discussed in detail, including warnings about possible shortcomings. At the same time, new modelling techniques are proposed, which could enable specific information to be extracted, from the limited and less accurate observations, like the degree of localization of double bonds, which is fundamental to the scientific case under examination.